Presenting an Online Impulsive Buying Decision Model with a Neuromarketing Approach - Afqahi, Hosna; Makizadeh, Vahid; Ghafournia, Mohammad (Management Strategies and Engineering Sciences, 2025)
The purpose of this study is to design an online impulsive buying decision model with a neuromarketing approach. The present research is applied in nature; qualitative in terms of method and approach; inductive in orientation; interpretive in paradigm; and employs grounded theory as its research strategy. The data collection sources include a review of theoretical foundations and interviews. The statistical population consists of experts in the field of neuromarketing (those with publications and articles in the specialized domain), university professors specializing in marketing, and psychologists active in the field of neuromarketing. Using a purposive non-probability snowball sampling method, the opinions of 15 participants were gathered through semi-structured interviews until theoretical saturation was achieved. Data analysis was conducted using MAXQDA software and involved three coding stages: open coding, axial coding, and selective coding. The research findings led to the identification of 19 main categories and 69 subcategories. These were incorporated into a paradigm model, with online impulsive buying decision-making as the core category, and included causal conditions (cognitive factors, impuslive factors, personality factors, and old brain stimuli), contextual conditions (environmental factors, situational factors, marketing-oriented factors, demographic factors, and cultural factors), intervening conditions (economic factors, ethical factors, and technical factors), strategies (utilizing neuroscience tools and employing neuromarketing), and consequences (analyzing consumers' impuslive behavior, optimizing customer relationships, creating effective advertisements, increasing online impulsive sales, and optimizing branding).